Cranberry: A Promising Natural Source of Potential Nutraceuticals with Anticancer Activity - Mantzorou, Maria; Zarros, Apostolos; Vasios, Georgios; Theocharis, Stamatios; Pavlidou, Eleni; Giaginis, Constantinos (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Studies have shown that cranberry and its components may exert anticancer properties. The present study aims to critically summarise the existing experimental studies evaluating the potential effects of cranberry on cancer prevention and treatment. PubMed database was searched to identify relevant studies. Current in vitro studies have indicated that cranberry and/or its components may act as chemopreventive agents, diminishing the risk for cancer by inhibiting cells oxidation and inflammatory-related processes, while they may also exert chemotherapeutic effects by inhibiting cell proliferation and angiogenesis, inducing cell apoptosis and attenuating the ability of tumour cells to invade and metastasis. Limited in vivo studies have further documented potential anticancer activity. Cranberry could be considered as a conglomeration of potential effective anticancer druglike compounds.
Keywords: Cancer